Non-medical Use of Prescription Drugs and its Association with Socio-demographic Characteristics, Dietary Pattern, and Perceived Academic Load and Stress in College Students in Puerto Rico - Betancourt, Jesmari; Ríos, Josué L.; Pagán, Ideliz; Fabián, Carla; González, Anaisa M.; Cruz, Sonia Y.; González, Michael J.; Rivera, Winna T.; Palacios, Cristina (Puerto Rico Health Sciences Journal, 2013)
Objective: Stress can have deleterious effects on health and academic performance. Common stress-relieving activities among college students include the non-medical use of prescription drugs (NMUPD). The aim of this study was to determine the associations between self-perceived academic load and stress, NMUPD (stimulants, depressants, and sleeping medication), and dietary pattern in college students in PR. Methods: A questionnaire to evaluate academic load and stress, NMUPD, and dietary pattern was used on a representative sample of 275 first- and second-year students from one campus. Results: In total, 27.6% reported NMUPD in the past 6 months, with higher use among students aged 21-30 years (93.4%) than in those aged 31-53 years (6.6%; p=0.062). Those with high levels of stress had higher NMUPD (42.1%) than did those with low (26.3%) or moderate (31.6%) stress levels, after controlling for age and sex (p=0.03). Among those who reported NMUPD over the previous 6 months, 74% reported that such use was effective as a coping strategy, and 35% reported that it helped them to improve academic performance. Although no significant association was found between NMUPD and dietary pattern, 57% of the participants reported that their appetites decreased when they engaged in NMUPD. Conclusion: To our knowledge, this is the first study that has associated selfperceived academic load and stress, NMUPD, and dietary pattern among college students in Puerto Rico. NMUPD’s prevalence was 27.6%, which prevalence appeared to be higher in students aged 21-30 years than in those of any other age. High levels of stress were significantly related to high NMUPD in this sample.